INTEGRATED ULTRASONIC-CAPACITANCE LIQUID LEVEL SENSOR - ABD GHANI, ABDUL FATAH FIKRI (Universiti Teknologi PETRONAS, 2017)
Ultrasonic-Capacitance Integrated Liquid Level Sensors in oil storage using ultrasonic and capacitance primary objective is to propose combination of technique or system that is robust enough to measure the total liquid level and oil-water interface level in crude oil tank by assuming the clear separation between water and crude oil. In this case, a conventional capacitance oil-water interface level sensor is not robust enough to give accurate oil-water interface when the tank is not full. Plus, the conventional capacitance oil-water interface level sensor working principle ignores the capacitance of oil by assuming the total effective capacitance is equal to water level due to huge differences between oil and water dielectric permittivity. The risk of safety issue such as overflow of tank has not been considered. The aim of a capacitance probe is to measure the oil-water interface level in crude oil tank in real time and an ultrasonic level sensor to measure the total liquid level in crude oil tank.